2020
DOI: 10.1177/0011128720981898
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Terrorism and Attitudes Toward Refugees: An Empirical Test of Group Threat Theory

Abstract: In recent years, the co-occurrence of the migration crisis and terrorist attacks in European cities have created a strong link between refugees and asylum seekers and terrorism in the minds of many Europeans. This study investigates how attitudes toward refugees are associated with fear of terrorism. Using multilevel modelling on 1,500 Belgian citizens nested in 402 municipalities, results indicate that positive attitudes toward refugees are associated with lower terrorism fear. Adverse economic conditions at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Because of humanitarian concerns, many are willing to help refugees; however, because of national interests (e.g., bogus asylum claims), some are concerned about admitting refugees (Jeannet et al, 2021). More precisely, the rather limited amount of research on refugee and asylum policy preferences finds that a heightened sense of humanitarianism (Fraser and Murakami, 2022), low fear of terrorism (De Coninck, 2020), identification with left-leaning and green-leaning parties (Gravelle, 2019), and being a citizen of an extensive welfare state and a historically immigration-oriented country (Koos and Seibel, 2019) are positively associated with a preference for liberal refugee and asylum policies.…”
Section: Design Data and Methodsmentioning
confidence: 99%
“…Because of humanitarian concerns, many are willing to help refugees; however, because of national interests (e.g., bogus asylum claims), some are concerned about admitting refugees (Jeannet et al, 2021). More precisely, the rather limited amount of research on refugee and asylum policy preferences finds that a heightened sense of humanitarianism (Fraser and Murakami, 2022), low fear of terrorism (De Coninck, 2020), identification with left-leaning and green-leaning parties (Gravelle, 2019), and being a citizen of an extensive welfare state and a historically immigration-oriented country (Koos and Seibel, 2019) are positively associated with a preference for liberal refugee and asylum policies.…”
Section: Design Data and Methodsmentioning
confidence: 99%
“…Study 2 deals with the impact such differences in news supply/content may have on fear of terrorism among broadsheet and tabloid readers. Research has shown that attitudes towards immigration and refugees are associated with fear of terrorism in Belgium (De Coninck, 2020). Hence, fear of terrorism is one of the potential tokens of right-leaning political choices.…”
Section: Hypothesesmentioning
confidence: 99%
“…Extrapolated to the context of terrorism news coverage, non-Muslim news consumers’ perceived identification should be lower when the victims are categorized as Muslims rather than non-Muslims (Dumont et al, 2003; Gordijn et al, 2001). Although non-Muslim news consumers do not represent a uniform group, their perceived identification with other non-Muslim ingroup members may increase under the perceptions of threat (Brewer, 1993; De Coninck, 2020; Rothgerber, 1997). Hence, based on the assumptions of SIT, we assume that emotional reactions may vary as a function of the perception of the victims as ingroup or outgroup members (Gordijn et al, 2001).…”
Section: Identification With the Victims In Terrorism News Coveragementioning
confidence: 99%
“…Recent attacks such as the 2019 Sri Lanka Easter bombings, the 2016 Christmas market attack in Berlin or the 2017 Manchester bombing have fueled public fears of terrorism and have made terrorism a prominent issue in international news coverage. However, the repeated association of negative attributes such as terrorism crimes and radicalism with Islam has also led to the perception of Muslims as threatening outgroup members (De Coninck, 2020; Velasco Gonzalez et al, 2008; Matthes et al, 2019; von Sikorski et al, 2021). In this context, terrorist crimes specifically targeting Muslims in Western societies have increased during the past years in Western countries (Kanji, 2018).…”
mentioning
confidence: 99%